2021
DOI: 10.1002/ffj.3688
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of aroma‐active compounds to the aroma of Lu'an Guapian tea

Abstract: Lu'an Guapian (LAGP) tea, produced in Lu'an, Anhui province, is among the ten most popular teas in China. 1 LAGP tea is the only tea produced in China that consists of tender leaves and has no tea buds or stems. Its production requires de-enzyming, shaping, first drying, second drying, and final drying (Figure 1). It is worth noting that the drying processes of LAGP, which are different from those of other green teas, contribute to the characteristic aroma and taste of the tea. 2 "Sensomics" was proposed by Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Based on OAV calculation, nonanal, linalool, (Z)-jasmone, and methyl jasmonate were the key odorants in premium green teas (Longjing, XYMJ, Taiping Houkui, Lu’an Guapian, etc.) [ 11 , 35 , 36 , 37 ]. Cis-3-hexenyl hexanoate in XYMJ green tea was determined by both OAV calculation and GC-O, while (+)-δ-cadinene was only detected by OAV calculation, which might be due to the different sample preparation techniques [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on OAV calculation, nonanal, linalool, (Z)-jasmone, and methyl jasmonate were the key odorants in premium green teas (Longjing, XYMJ, Taiping Houkui, Lu’an Guapian, etc.) [ 11 , 35 , 36 , 37 ]. Cis-3-hexenyl hexanoate in XYMJ green tea was determined by both OAV calculation and GC-O, while (+)-δ-cadinene was only detected by OAV calculation, which might be due to the different sample preparation techniques [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al 28 found that geraniol was one of the key compounds in the formation of black tea aroma, and its content determines the intensity of black tea aroma. Xiao et al 29 found that the aroma of yellow tea was mainly formed by six compounds with OAV values greater than 1, including geraniol, α‐pinene, trans‐β‐ionone, etc. Niu et al 30 analyzed the contribution of main aroma compounds in different black tea to aroma intensity and found that geraniol and methyl salicylate were the most significant compounds in black tea, and geraniol had the highest contribution.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of tea aroma characteristics was closely related to the types of volatile compounds, and there were certain differences in the volatile compounds that formed the aroma characteristics of different tea, thus forming the unique aroma of different tea. For example, the main compounds forming the aroma characteristics of black tea were geraniol and methyl salicylate, the content of which determined the aroma intensity of black tea ( Huang et al, 2022 , Niu et al, 2022 ), Geraniol and trans -β-Ionone were the main compounds that formed the aroma characteristics of yellow tea ( Xiao et al, 2022 ). Secondly, many scholars analyzing tea aroma compounds and found that geraniol, trans -β-Ionone, nerol, citronellol, benzeneacetalidol and trans -nerolidol were the main compounds responsible for tea aroma, but there were certain differences between different kinds of tea ( Li and Wang, 2020 , Ma et al, 2018 , Zhou et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%